A positively charged small-molecule T1 magnetic resonance imaging contrast agent for highly efficient labeling and tracking adipose tissue-derived stem cells. (December 2020) - Mao, Zheng; He, Yilin; Zhao, Hongbo; Zhang, Ye; Yin, Jingbo; Cao, Yi; Pei, Renjun
Graphical abstract: Highlights: A small molecule T1 contrast agent with positive charge (Gd-HP-DO3A-TA) was prepared. Gd-HP-DO3A-TA was efficiently internalized by adipose-derived stem cells (ADSCs). Gd-HP-DO3A-TA exhibited good biocompatibility in vitro. Gd-HP-DO3A-TA-labeled ADSCs showed good contrast effect. Abstract: Stem cells have great promise in regenerative medicine, and in vivo visualization of transplanted stem cells with noninvasive technique is essential for tracking and monitoring cell behaviors. Herein, a small-molecule T1 contrast agent with positive charge was prepared for efficiently labeling adipose-derived stem cells (ADSCs) in vitro and in vivo. The contrast agent was synthesized by conjugating quaternary ammonium salt onto DO3A (1, 4, 7, 10-tetraazacyclododecane-1, 4, 7-triacetic acid) skeleton via nucleophilic reaction, then chelating gadolinium ion to form Gd-HP-DO3A-TA complex. The Gd-HP-DO3A-TA exhibited a similar longitudinal relaxivity (4.42 mM −1 s −1 ) as commercial contrast agent (Gd-DTPA), but it can be efficiently internalized by ADSCs, leading to remarkably enhanced cellular magnetic resonance imaging (MRI) signal intensity without negative effects on viability, proliferation and multi-differentiation potential of ADSCs. Moreover, in vivo experiments revealed that Gd-HP-DO3A-TA-labeled ADSCs can home to the injured liver region with enhanced signal contrast and promote to rebuild liver function. Our results indicate that the small-molecule T1 contrast agent with positive charge has great potential for stem cells labeling and MRI tracking.